Tutankhamun in Portugal: reports in the portuguese press (1922-1939): a contribution to ancient Egypt reception studies - Sales, José das Candeias (2020)
In any science or field of knowledge, the conceptual and terminological definition is essential for understanding the issues under study and for communicating the related research results. This, of course, also applies to the field of reception of ancient Egypt. The main goal of this text is to analyse, define and organise the set of concepts, notions and terms existing within the reception studies of ancient Egypt, namely Egyptomania, Egyptophilia, Egyptian Revival, Tutmania, Mummymania and Amarnamania. At the same time, resorting to our Research Project Tutankhamun in Portugal. Reports in the Portuguese press (1922-1939), we intend to demonstrate how the press, in this case of the early 20th century, constitutes simultaneously a manifestation and an agent of the reception of ancient Egypt in Portugal.